2016
DOI: 10.1007/s11701-016-0616-6
|View full text |Cite
|
Sign up to set email alerts
|

Da Vinci© Skills Simulator™: is an early selection of talented console surgeons possible?

Abstract: To investigate whether the learning curve of robotic surgery simulator training depends on the probands' characteristics, such as age and prior experience, we conducted a study of six distinct proband groups, using the da Vinci Skills Simulator: experienced urological robotic surgeons, surgeons with experience as da Vinci tableside assistants, urological surgeons with laparoscopic experience, urological surgeons without laparoscopic experience, and complete novices aged 25 and younger and 40 and older. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…These comparisons should be cautiously interpreted due to the potential type II error caused by the small sample size and non-parametric testing procedure. These results, however, correlate to a study by Meier et al investigating the learning curve of incorporating robotic surgery simulator training with surgeons of different ages and prior expertise, which demonstrated that, regardless of the level of training, all learners can benefit from training via robotic simulation [15]. Of note, the majority of attending physicians reported during the debriefing that had the bedside assistant been a resident physician, the surgeon would have instructed the resident to begin laparotomy earlier.…”
Section: Discussionsupporting
confidence: 83%
“…These comparisons should be cautiously interpreted due to the potential type II error caused by the small sample size and non-parametric testing procedure. These results, however, correlate to a study by Meier et al investigating the learning curve of incorporating robotic surgery simulator training with surgeons of different ages and prior expertise, which demonstrated that, regardless of the level of training, all learners can benefit from training via robotic simulation [15]. Of note, the majority of attending physicians reported during the debriefing that had the bedside assistant been a resident physician, the surgeon would have instructed the resident to begin laparotomy earlier.…”
Section: Discussionsupporting
confidence: 83%
“…Regardless of a practitioner's age or conventional surgical training, good training and continued practice are required to perform safe and effective surgery with these systems. 35,59 A control system that instead translates commands from natural human hand motion to robotic mechanical output with high fidelity would seem desirable. Such technologies are in development, predominantly for patients who have undergone amputations.…”
Section: Control Systemsmentioning
confidence: 99%
“…[49] Subsequently, Mimic and Intuitive Surgical Inc. released the da Vinci Skills Simulator that is specifically designed to allow surgeons to improve their proficiency before carrying out real operations. [50] Although other surgical systems have been developed to provide additional surgical options for patients such as EndoMaster, Medrobotics, Microbot Medical, and Titan Medical, the da Vinci system is still the most popular with over 875 000 da Vinci procedures performed in 2013, up from 523 000. [33] These emerging systems will offer a variety of choices, versatility, and functions in the competitive surgical sector market.…”
Section: Robot-assisted Surgerymentioning
confidence: 99%